Practical management of myelofibrosis with ruxolitinib. Issue 12 (December 2015) - Ho, P. J.; Marlton, P.; Tam, C.; Stevenson, W.; Ritchie, D.; Bird, R.; Dunlop, L. C.; Durrant, S.; Ross, D. M.
Abstract: Treatment for the majority of patients with myelofibrosis is primarily based on symptom control as curative allogeneic stem cell transplantation is typically offered only to younger patients, especially those with poor prognosis disease. Around 50% of patients with myelofibrosis have the JAK2 V617F mutation, but almost all patients have aberrant activation of the JAK‐STAT signalling pathway. Recent efforts have focussed on the clinical use of JAK2 inhibitors to treat myelofibrosis. In this article, we present our recommendations for the practical management of myelofibrosis with ruxolitinib, a selective inhibitor of both JAK1 and JAK2. Ruxolitinib can significantly improve the quality of life of patients with myelofibrosis. There is also increasing evidence of a positive impact on survival. Consistent with the physiological role of JAK signalling the major toxicity of ruxolitinib is cytopenia. Managing cytopenia is key to maximising the therapeutic benefit of ruxolitinib. Further research into the safety of ruxolitinib in patients with thrombocytopenia is warranted, as is its role in special subgroups of patients, such as those undergoing stem cell transplantation and those experiencing thrombosis as a major manifestation of myelofibrosis.